Implementasi Pelaksanaan Program Kampus Mengajar Angkatan 7 di UPT SPF SD Inpres Mariso 1 Makassar - Sanreni Naba; Hurriah Ali Hasan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This activity aims to provide students with the opportunity to develop themselves through activities and creativity outside the scope of lectures and to be in the field under various conditions of schools throughout Indonesia. The research method used is a qualitative approach. The subjects of this research are all students of UPT SPF SD Inpres Mariso 1. The object of the research is the implementation of the Campus Teaching Program at UPT SPF SD Inpres Mariso 1, Data collection was carried out using observation and documentation techniques. From the results of the observations, it can be concluded that the teaching and learning activities at the school are quite good. The use of technology is also running quite well, although its implementation is not as frequent as literacy and numeracy activities, which make students fond of reading. In character development activities, students no longer engage in bullying other students, and the Ramadan Fest activities made students more confident to perform in public and improved their abilities in religious fields. The results of extracurricular activities such as Flag Ceremony Training, Morning Exercise, Clean Saturday, Market Day, Traditional Games, and Arts and Culture Performances ran smoothly. After these activities, students became more disciplined, able to manage finances, and significantly increased their creativity. Following the implementation of these activities, we hope that students with abilities in related fields will continue to receive guidance and attention.